The Racialized Glass Escalator and Safety Net: Wages and Job Quality in "Meds and Eds" among Working-Class Men. (12th November 2020) - Dill, Janette; Hodges, Melissa J
Abstract: Past research has shown that minority men are more likely than others to enter female-dominated occupations, but less is known about the quality of their jobs in these fields in contrast to other employment options. We use the 2004 and 2008 panels of the Survey of Income and Program Participation (SIPP) to examine whether the female-dominated industries of education and health care produce better job quality in terms of wages, benefits, hours, and job security for working-class men relative to other industries, with emphasis on differences by race-ethnicity. We find that although workers in the education and health care industries fared better during the Great Recession compared to those in other industries, effects for wages, health insurance, hours, and layoff for working-class Men of Color were substantially lower compared to those of White men. We find strong evidence of a racialized glass escalator, but also a racialized safety net in the care sector post-recession: the health care and education industries provide better job quality for White men than for Men of Color, though they are less likely to be in these jobs, and these sectors were more protective of White men as compared to minorities during the recession.